Management of aneurysmal subarachnoid hemorrhage: a national survey of current practice. (20th October 2014) - Al-Helli, Othman; Bush, Steven; Ingale, Harshal; McConachie, Norman
Abstract : Objectives: The Royal College of Physicians and American Heart Association/American Stroke Association published recommendations in 2012 for the management of aneurysmal subarachnoid hemorrhage (aSAH). This was followed by recommendations included in the National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report published in November 2013. The aim of this study was to assess how many of these recommendations were being followed across the UK and Ireland 6 months after publication of the latest recommendations, and to compare current practice with the NCEPOD data collected in 2011. Methods: We formulated a survey composed of 19 questions regarding the management of aSAH, and conducted a telephone interview with the neurosurgical registrars on call. Results: 22 out of 30 centers aimed to treat ruptured aneurysms by coiling or clipping within 48 h from ictus, yet only 15 units offered regular weekend interventional neuroradiological treatment. In 9 units, all aSAH patients were routinely discussed in a multidisciplinary meeting. Conclusions: At 6 months following publication of the NCEPOD report we found that in the majority of neurosurgical units, most of the key recommendations were being met. However, in the remainder there was variability in clinical practice.